Participatory varietal selection in high-potential production systems - Witcombe, John R. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
This paper reviews some of the participatory research in high-potential production systems on participatory varietal selection in high-potential production systems. This collaborative research is conducted by the Centre for Arid Zone Studies, UK; Local Initiatives in Biodiversity Research and Development (U-BIRD), Nepal; the Gramin Vikas Trust, India; and the Punjab Agricultural University, India.